BACTERIOLOGICAL ANALYSIS OF AIR (AEROMICROFLORA) FROM THE LEVEL OF DENTAL OFFICES IN IAŞI COUNTY - E. R. Cernei; Dana Cristiana Maxim; R.Mavru; L. L. Indrei (Romanian Society of Oral Rehabilitation, 2014)
Aim of the study This baseline study aims investigate the appreciation regarding of the microbial charge of the air (aeromicroflora) from the treatment rooms of dental cabinets. Material and methods The method used is the Koch sedimentation method (sedimentation only of large sized particles).The sedimentation method consisted in the exposure on Petri dishes, of a given diameter, which contain a nutrient environment appropriate for the bacteria whose presence and density we wished to assess. The appreciation of the degree of bacterial contamination of the air (microaeroflora) was conducted by means of the contamination bacteriological indicators (TGN incubated at 370C, hemolytic streptococci, staphylococci and coliforms). Results It can be noticed that in school/university dental cabinets there is a high bacterial density, the air being charged with human origin flora, pathogen or conditionally pathogen bacteria being potentially present. Conclusions The presence of conditionally pathogen bacteria in the environment of school/university dental cabinets constitutes a higher risk than their presence in the dental cabinets for adults, due to the incomplete development and maturity of the young, whose receptivity to infection is higher.